Menopause, Menopause - Samsioe, Göran (Mosby, 2003)
Rapid Reference to HRT will provide the reader with authoritative and accessible information from a clinical expert in the field, to assist with treatment decisions. Each title in the new Rapid Reference series provides standard core content (epidemiology - management/ therapy) combined with the additional information, such as FAQs and patient organisations, needed by the GP to provide effective patient care. They also include drugs listings, clinical trials, information on future developments and web site listings to keep the reader up to speed with new developments and to extend their knowledge of the disease area. the book also provides an interdisciplinary approach to diagnosing, treating, and managing the symptoms of menopause. Emphasizes the use of hormone replacement therapy along with the practical considerations needed before prescribing HRT